Laser all‐ceramic crown removal—A laboratory proof‐of‐principle study—Phase 1 material characteristics. Issue 8 (13th August 2014) - Rechmann, Peter; Buu, Natalie C.H.; Rechmann, Beate M.T.; Le, Charles Q.; Finzen, Frederick C.; Featherstone, John D.B.
<x xml:space="preserve">Abstract</x> Background and Objectives The removal of all‐ceramic crowns is a time consuming and destructive procedure in the dental office. The removal of all‐ceramic crowns using Er:YAG lasers has not been previously described in the scientific literature. The objective of this laboratory proof‐of‐principle study was to evaluate whether with regards to absorption and transmission characteristics of bonding cements and ceramics all‐ceramic crowns can be removed from natural teeth using an Erbium laser. Study Design/Materials and Methods The Fourier Transform Infrared Spectroscopy (FTIR) was used on flat ceramic samples (IPS Empress Esthetic (EE), E.max CAD, and E.max ZirCAD) to assess which infrared laser wavelengths transmit through the ceramics. Additionally, FTIR spectra for four bonding cements (Variolink Veneer, Variolink II, Multilink Automix, and SpeedCEM) were obtained. The Er:YAG laser energy transmission (wavelength 2, 940 nm, 10 Hz repetition rate, pulse duration 100 µs at 126 mJ/pulse to 300 µs at 508 mJ/pulse) through different ceramic thicknesses was measured. Ablation thresholds for bonding cements were determined. Cement samples were directly irradiated or laser light was transmitted through ceramic samples. Results While the ceramics did not show any characteristic water absorption bands in the FTIR, all bonding cements showed a broad H2O/OH absorption band. Some cements exhibited a distinct absorption peak at the Er:YAG laser emission wavelength. Depending on the ceramic thickness, EE and E.max CAD ceramics transmitted between 21 and 60% of the incident Er:YAG energy, with E.max CAD transmitting more energy than EE at comparable thicknesses. In contrast, E.max ZirCAD transmitted only 5–10% of the incident energy. Initial signs of cement deterioration occurred at 1.3–2.6 J/cm2. Multilink Automix, SpeedCEM, and Variolink II started ablation at 4.4–4.7 J/cm2. Variolink Veneer needed 44% less energy for ablation. Conclusion Er:YAG laser energy can be transmitted through all‐ceramic materials and those transmitted energies are sufficient for ablation of bonding cements. Lasers Surg. Med. 46:628–635, 2014. © 2014 Wiley Periodicals, Inc.